Two-orders of magnitude enhanced droplet energy harvesting via asymmetrical droplet-electrodes coupling. (April 2023) - Zhao, Zhipeng; Li, Huizeng; Li, An; Liu, Lu; Xue, Luanluan; Cai, Zheren; Yuan, Renxuan; Yu, Xinye; Song, Yanlin
Abstract: The collection and utilization of water power as clean energy have made tremendous progress in recent years, where the droplet-based triboelectric power generation is one of the most studied fields. Current researches mainly focus on the droplet-based single-electrode triboelectric generation mode; however, the low power output greatly limits the practical applications. By contrast, the droplet-based bi-electrode freestanding TENG (DBE-TENG) show great potential for enhancing the output, while the charge transfer mechanism of droplets evolution on the DBE-TENG is still ambiguous. Here we demonstrate that for a DBE-TENG, the maximum current output of the droplet at different droplet impact positions exhibits a sinusoidal-like variation, and the current output can be improved by two orders of magnitude by simply controlling the droplet impacting positions. Furthermore, an asymmetrical-capacitance-induced charge transfer mechanism is proposed, which well elucidates the prominent current output enhancement and the sinusoidal-like variation. In addition, the current output enhancing strategy is applicable under different kinds of dielectric materials and conditions (inclined conditions and different Weber numbers), with the maximum enlargement up to 263 times. The findings deepen the understanding of the charge transfer mechanism for bi-electrode triboelectric nanogenerators, and will be of significance for improving the efficiency of sustainable energy harvesting. Graphical Abstract: The maximum current output of the droplet impacting on positions exhibits a sinusoidal-like variation, and the current output can be improved by two orders of magnitude by simply controlling the droplet impacting positions on the double-electrodes triboelectric nanogenerator. An asymmetrical-capacitance-induced charge transfer mechanism is proposed, which well elucidates the prominent current output enhancement and the sinusoidal-like variation. The current output enhancing strategy is applicable under different kinds of dielectric materials and conditions with the maximum enlargement up to 263 times. ga1 Highlights: The current output can be improved by two orders of magnitude by regulating the droplet positions. Asymmetrical-capacitance-induced charge transfer mechanism dominates the power output. The maximum current output at different droplet impact positions exhibits a sinusoidal-like variation . The current enhancing strategy is universal under different dielectric materials and conditions .